Training and Marketing of Fashion Upcycling Products in Local Communities - Monica Hartanti; Elizabeth Wianto (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
This article focuses on the implementation of Sustainable Development Goal 12 (SDG 12), about responsible consumption and production, particularly the fifth target of reducing waste production through prevention, reduction, recycling, and reuse. The study explored and evaluated the results of the product upgrading performed in a community empowerment activity, which involved upcycling denim waste into A-line skirts and tote bags, and adding decorative materials using sewing techniques such as decorative stitches, tie-dye, and macrame. The article also discusses the importance of producing goods with greater value in terms of sustainability in natural resource utilization. On-site surveys were conducted to evaluate the results of the product upgrading, and the survey results were analyzed qualitatively for further sustainability efforts related to upcycling. Overall, 15 buyers participated, and the results showed positive perceptions about the use of products from fashion waste and there is interest in participating in similar activities in the future.